A Prospective Cohort Study of Symptomatic Venous Thromboembolic Events in Foot and Ankle Trauma: The Need for Stratification in Thromboprophylaxis?. Issue 1 (19th August 2016) - Blanco, Jose A.; Brocklesby, Gemma; Mangwani, Jitendra
Category: Trauma Introduction/Purpose: The incidence of Venous Thromboembolism (VTE) and the balance of risks and benefits associated with chemical thromboprophylaxis in foot and ankle trauma are controversial, and much less investigated than in hip and knee surgery. A recent systematic review showed a low VTE rate in foot and ankle surgery (0-0.55%), but with an increased incidence in foot and ankle trauma, the highest in TA rupture and surgery. This study compares the 90-day VTE rates of 3 cohorts of patients: Group 1: TA ruptures managed in a full weight bearing (FWB), functional, Vacoped™ protocol over an 8 week period; Group 2: Stable ankle fractures managed in NWB below knee casts for 6 weeks; Group 3: Unstable or displaced ankle fractures managed with surgery and NWB below knee casts for 6 weeks. Methods: The data was extracted from two prospectively collected databases, one for the acute TA ruptures between March 2010 and December 2014, and one for ankle fractures from October 2013 to April 2014. These datasets were cross validated with the hospital VTE database. All patients were risk assessed at the time of presentation to the hospital. Selective chemical thromboprophylaxis was prescribed for patients with the previous history of VTE and patients who were deemed high-risk on VTE assessment. 90-day incidence of symptomatic VTE was drawn from the hospital radiology database. Results: Group 1: Overall VTE rate of 4.9% at a mean of 16.1 days. 3 Pulmonary Embolism (PE) and 11 Deep Vein Thrombosis (DVT). Total number of 283 patients. Group 2: Overall VTE rate of 2.2% at a mean of 33.4 days. 5 DVT. Total number of 227 patients Group 3: Overall VTE rate of 3.0% at a mean of 37.2 days. 1 PE and 5 DVT. Total number of 199 patients. Symptomatic VTE presents significantly earlier in acute TA rupture than ankle fracture patients (p=0.002) Conclusion: Although the overall incidence of VTE in foot and ankle trauma is low., there is a relatively higher incidence of VTE in patients with acute TA ruptures. This is, in spite of recent early weight bearing regimens. This study also shows that occurrence of symptomatic VTE in patients with Acute TA rupture happens much sooner compared to the ankle fracture patients. Although the exact reason for this difference in time of presentation of VTE is unknown, it may be due to de-functioning of the calf muscle pump immediately after the acute TA rupture.